Antický Rím : (Tutto su Roma antica) - Giannelli, Giulio: 1889-1980; Paoli, Ugo Enrico: 1884-1963; Arias, Paolo Emilio; Carcopino, Jerome; kolektív autorov; Škorupová, Anna; Šafár, Ignác: 1912-1981; Smolák, Štefan; Grečnerová, Božena (Výtvarná redakcia, 1967)
Rozdelené na všetky stránky života: vzdelávanie, vojna, jedlo, kultúra, ...